The Influence of Atopy History on Sensitive Skin: A Systematic Review - Fatahillah, Walid Rivaldi (Jurnal Biologi Tropis, 2024)
Epidemiological studies suggest a strong correlation between a history of atopy and the likelihood of developing sensitive skin. This article aims to explore the physiological mechanisms linking these two conditions. A systematic review was conducted from relevant literature using PubMed, Google Scholar, and ProQuest, with search terms such as “atopy OR atopic OR atopy history AND sensitive skin OR sensitive skin syndrome.” The findings reveal that filaggrin mutations in individuals with atopy compromise skin barrier integrity, while Th2 cytokines exacerbate inflammatory responses and hinder epidermal regeneration, thereby increasing vulnerability to irritants. These insights underscore the significant role of genetic predisposition and immune dysregulation in the higher prevalence of sensitive skin among individuals with a history of atopy.